2023
DOI: 10.1177/01461672221140269
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Among Friends Serves as a Social Prior: The Assumption That “Birds of a Feather Flock Together” Shapes Social Decisions and Relationship Beliefs

Abstract: Social interactions unfold within networks of relationships. How do beliefs about others’ social ties shape—and how are they shaped by—expectations about how others will behave? Here, participants joined a fictive online game-playing community and interacted with its purported members, who varied in terms of their trustworthiness and apparent relationships with one another. Participants were less trusting of partners with untrustworthy friends, even after they consistently showed themselves to be trustworthy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…They judged the inconsistent person as less trustworthy than a consistent person, including judging the former as untrustworthy and the latter as trustworthy. These findings complement research which shows that adults use the consistency principle to judge the trustworthiness of others as it pertains to consistencies between: (a) apologies and subsequent behavior (Hui et al, 2011) and (b) personal trustworthiness and trustworthiness of friends (Schwyck et al, 2023). The findings complement the findings that adults conceptualize hypocrisy as the inconsistency between personal standards and behavior when standards are presented first (Barden et al, 2005;Laurent & Clark, 2019).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…They judged the inconsistent person as less trustworthy than a consistent person, including judging the former as untrustworthy and the latter as trustworthy. These findings complement research which shows that adults use the consistency principle to judge the trustworthiness of others as it pertains to consistencies between: (a) apologies and subsequent behavior (Hui et al, 2011) and (b) personal trustworthiness and trustworthiness of friends (Schwyck et al, 2023). The findings complement the findings that adults conceptualize hypocrisy as the inconsistency between personal standards and behavior when standards are presented first (Barden et al, 2005;Laurent & Clark, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…( 2019) found that older, but not younger, children recognized hypocrisy as demonstrated in their judgments of the characteristics of others who showed inconsistency between their behavior and moral standards. The use of the consistency principle in trustworthiness judgments has been found in adults for various social behaviors (e.g., Hui et al., 2011; Schwyck et al., 2023) and in older children rather than young children when judging temporal consistency and verbal‐nonverbal consistency (Rotenberg et al., 1989; Rotenberg & Pilipenko, 1984). The current research provides unique findings, however.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consistency of trait and behavioral information aids in social stereotyping which shapes person perception and determines what we specifically remember about others (Cantor & Mischel, 1977;Hastie et al, 2014;Hastie & Carlston, 1980;Quinn et al, 2007). People are also more likely to infer friendships between two individuals who share similar preferences and belong to similar social groups (Son et al, 2021) or demonstrate similar behavior in a game (Schwyck, Du, Li, et al, 2023). In other words, people, just like "items" in classic memory tasks may be distilled into a multidimensional feature vector of person-specific attributes that serve to organize social knowledge and predict behavior (Hamilton et al, 1980;Stolier et al, 2020;Uleman & Kressel, 2013).…”
mentioning
confidence: 99%